2020
DOI: 10.1159/000505641
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast-Derived Exosomes Contribute to Development of a Susceptible Substrate for Atrial Fibrillation

Abstract: Objective: Atrial fibrosis plays a critical role in atrial fibrillation (AF). A key event in the pathogenesis of fibrosis is the activation of fibroblasts (FBs) into myofibroblasts (MFBs). Paracrine factors released from MFBs lead to ion channel expression changes in cardiomyocytes (CMs). Downregulation of L-type calcium channel Ca v 1.2 expression is a hallmark of AF-associated ionic remodeling. However, whether exosome (Exo)-mediated crosstalk between MFBs and CMs regulates Ca v 1.2 expression remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…The changes in AERPs could be related to some ion channel-related miRNAs contained in exosomes. A previous study also showed that Ang II-treated cardiac fibroblast-derived exosomes contained miR-21-3p, which could regulate the expression of Cav1.2 and contribute to the development of a susceptible substrate for atrial fibrillation (13). However, we did not further explore the mechanism by which inhibition of exosome release directly changed AERPs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The changes in AERPs could be related to some ion channel-related miRNAs contained in exosomes. A previous study also showed that Ang II-treated cardiac fibroblast-derived exosomes contained miR-21-3p, which could regulate the expression of Cav1.2 and contribute to the development of a susceptible substrate for atrial fibrillation (13). However, we did not further explore the mechanism by which inhibition of exosome release directly changed AERPs.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, it has been demonstrated that, compared with the control group, the epicardial adipose tissue of patients with AF secretes more exosomes, and the expression of pro-inflammatory and pro-fibrotic factors is higher in exosomes (12). In addition, a recent study reported that myofibroblast-derived exosomes reduced the expression of voltage-gated L-type calcium channel subunit α1c (Ca v 1.2) and increased the vulnerability to AF (13). Based on these studies, we hypothesized that the increased secretion of exosomes was likely to promote AF.…”
Section: Introductionmentioning
confidence: 99%
“…They found that exosomes secreted by MFBs can act on cardiomyocytes (CMs) and cause the latter to down-regulate the expression of the L-type calcium channel Cav1.2, which is a typical AF-associated ionic remodeling marker. Further studies have shown the miR-21-3p in exosomes may be the inhibitory molecule responsible for this down-regulation ( 60 ). In addition, it has been observed that the lncRNA NRON (ncRNA repressor of the nuclear factor of activated T cells) can promote polarization of M2 macrophages to reduce atrial fibrosis, and a study by Li et al showed that exosomes are involved in this process.…”
Section: Diagnostic and Therapeutic Role Of Exosomes In Atrial Fibrillationmentioning
confidence: 99%
“…The miR-21-3p in exosomes has been shown to be related to the mechanism of AF ( 60 ). And many other miRNAs have been reported to be associated with AF.…”
Section: Non-coding Rnas In Atrial Fibrillationmentioning
confidence: 99%
“…For the sake of verifying the effects of MSCs-Exo on proliferation, phenotypic switching and secretion functions of broblasts, Ang-II was used to stimulate atrial broblasts (FBs) to trans-differentiate into myo broblasts (MFBs) [14]. The differentiation was con rmed using immuno uorescence staining for α-SMA, a speci c marker for MFBs.…”
Section: Mscs-exo Ameliorate Ang-ii-induced Proliferation Phenotypic Switching and Secretion Functions Of Broblastsmentioning
confidence: 99%